Electronic Origin of Out‐of‐Plane Distortions in Porphyrins. Issue 20 (4th June 2014) - Austeria, Muthu P.; Pancharatna, Pattath D.; Balakrishnarajan, Musiri M.
Abstract: Porphyrins are noninnocent ligands that facilitate redox processes in many biological reactions. Though the porphyrin dianion is planar and aromatic, in many instances, its skeleton exhibits a variety of out‐of‐plane (OOP) distortions, which are primarily attributed to steric factors. Nevertheless, these distortions are suspected to play a hidden role in their biochemical reactions, as the nature of the distortion is conserved for a specific functionality across species. The propensity of porphyrins to assist redox reactions remains mysterious, as oxidation and OOP distortions affect their aromaticity. Our quantum chemical modelling of the two‐electron oxidation of porphyrin reveals that there are definite electronic reasons behind OOP distortions. An extension of the frontier orbital model of Gouterman to include the occupied b1g, b2g and a1g (σ) molecular orbitals (MOs) is necessary to explain the nature and origin of OOP distortions. The distortions are the effect of the mixing of these σ‐type MOs with the π‐type a1u and a2u highest occupied molecular orbitals (HOMOs). These are further facilitated by the flexibility of the internal [16]annulene skeleton of the porphyrin framework. In the absence of transition metal ions, oxidation usually entails pronounced bond alternation along this internal cross owing to a1u /a2u mixing, which leads to the loss of aromaticity. However, this is accompanied by OOP distortions that help to retain the local aromaticity of the pyrrolic rings. Transition metal porphyrins with their energetically accessible d orbitals prefer OOP distortions over bond alternation and effectively conserve aromaticity. For late transition metal ions, the d 8 electronic configuration, which is ideal for a square‐planar complex, itself shows a variety of OOP distortions that stabilize the corresponding oxidation state through the mixing of the b1g MO with the a2u MO. For octahedral complexes with d 6 configuration of the central metal ion, a two‐electron oxidation is effectively supported by OOP distortions that result from the mixing of the b2g MO with the a2u MO. The a1u MO is usually less prone to mixing as it is concentrated far away from the central metal ion. Despite involving σ–π mixing, these OOP distortions conserve the aromaticity as shown by the computed chemical shifts of the optimized porphyrin systems. In addition to explaining the origin of the noninnocent nature of porphyrins, our results also provides a basis for the rational prediction and control of the OOP distortions to suite the desired biomimetic applications. Abstract : Out‐of‐plane distortions in porphyrins are found to be electronic in origin. The lowest unoccupied molecular orbitals (LUMOs) of various metalloporphyrins show the mixing of a porphyrin a2u molecular orbital with d   z   2 (a1g ), d xy (b2g ) and d   x   2 – y   2 (b1g ) orbitals to exhibit doming, ruffling and saddling, respectively. These distortions that retain aromaticity are attributed to σ–π mixing.